Ectopic expression of fungal EcGDH improves nitrogen assimilation and grain yield in rice - Tang, Dongying; Peng, Yuchong; Lin, Jianzhong; Du, Changqing; Yang, Yuanzhu; Wang, Dan; Liu, Cong; Yan, Lu; Zhao, Xiaoying; Li, Xia; Chen, Liangbi; Liu, Xuanming (Journal of integrative plant biology, 2018)
NADP（H）-dependent glutamate dehydrogenases（GDH） in lower organisms have stronger ammonium affinity than those in higher plants. Here we report that transgenic rice overexpressing the EcGDH from Eurotium cheralieri exhibited significantly enhanced aminating activities. Hydroponic and field tests showed that nitrogen assimilation efficiency and grain yields were markedly increased in these transgenic plants, especially at the low nitrogen conditions.These results suggest that EcGDH may have potential to be used to improve nitrogen assimilation and grain yield in rice.